Monitoring and engineering reactor microbiomes of denitrifying bioelectrochemical systems1. Issue 84 (16th September 2015) - Pous, N.; Koch, C.; Vilà-Rovira, A.; Balaguer, M. D.; Colprim, J.; Mühlenberg, J.; Müller, S.; Harnisch, F.; Puig, S.
<x xml:space="preserve">Abstract</x> Elucidating the structure–function relationship of a denitrifying biocathodes.